A comprehensive review of food fraud terminologies and food fraud mitigation guides. (February 2021) - Robson, Kelsey; Dean, Moira; Haughey, Simon; Elliott, Christopher
Abstract: Due to constant integrity challenges, ambiguous definitions, and lack of specific guidance, the food industry has been left vulnerable to food fraud. Food fraud is undefined by the EU, resulting in the creation of varying definitions from researchers and regulatory bodies. Not having a definition of food fraud and related terms makes it challenging to comprehend, communicate and ideate on how to prevent it. Furthermore, the food industry is lacking clear guidance on the prevention and mitigation of food fraud. Several documents are available to help guide the food industry; however, they are nonspecific to supply chains, which has left a substantial gap in knowledge that is necessary to protect the food supply. This review analyzed definitions for food fraud and related terms, as well as current guidance on food fraud prevention and mitigation, which can be utilized by the food industry to find commonality and assess where more information is needed. An abundance of literature describing food fraud was found, and although definitions varied, the common themes of intentional acts and economic motivation were widespread. Additionally, general guidance documents for food fraud mitigation and prevention shared general ideas of supply chain transparency, supplier audits, horizon scanning, and vulnerability assessment, which could be utilized throughout the food industry. Highlights: Food fraud definitions share common themes of intentional acts and economic motivation. . Lack of consistent 'types' of food fraud creates confusion over how fraud is described. Of the twelve food fraud mitigation documents found none focused on the beef supply chain.